Correlation Between Administrative Personnel Competency And Madrasah Administrative Personnel Performance - Badrudin Badrudin; Eneng Muslihah; Devita Komala; Mohd Fauzi Bin Hamat (Institut Agama Islam Negeri (IAIN) Curup, 2023)
The success of madrasas in achieving goals is strongly influenced by the madrasa climate, one of which is effective madrasa administration. To support the effective administration of madrasas, administrative staff are needed who have competence in accordance with the administrative staff standards set by the government. Therefore, the fulfillment of the qualification and competency standards for school/madrasah administrative staff must be met by school/madrasah administrators. Adequate competence of madrasah administrative staff will result in high performance of administrative staff. This study aims to describe the relationship between the Competence of Administrative Personnel and the Performance of Madrasah Administrative Personnel in Madrasah Tsanawiyah Negeri Bekasi City. This research is descriptive, using a quantitative approach to the type of correlation. Data collection techniques using a questionnaire questionnaire. Based on the results of the study, it is known that the competence of administrative staff has a significant relationship with the performance of madrasa administrative staff at Madrasah Tsanawiyah Negeri Bekasi City. Calculation of the correlation coefficient analysis shows the number 0.888, which means that there is a relationship with the